Am I a Public Servant or Am I a Pathogen? Public Managers’ Sector Comparison of Worker Abilities - Chen, Chung-An (2016)
Political rhetoric in the United States is rife with condemnations of public sector workers. The assertion that public sector workers are less creative, talented, or autonomous than those working in businesses pervades in both academic studies and public opinions. Facing constant criticisms, do public managers also perceive that government workers are less able than their private sector peers? If so, and more importantly, does the perceived inferiority of worker abilities shake their confidence, thereby undermining their work attitudes? The present study employs social comparison theory to answer these questions. Based on state government managers' responses in the United States, the results indicate that a clear majority of public managers perceive public sector inferiority with respect to worker creativity, talent, and autonomy. The findings also show that perceived inferiority is related to lower job satisfaction, job involvement, and pride in working for the current organization. Based on the findings, we provide suggestions to both researchers and practitioners.